2022
DOI: 10.1007/s13577-022-00758-6
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV alleviates senescence of vascular smooth muscle cells through activating Parkin-mediated mitophagy

Abstract: Astragaloside IV (AS-IV), as one of the main active components of Astragalus membranaceus, has been reported to have cardiovascular protective effects. However, the role and molecular mechanism of AS-IV in vascular senescence have not been clearly stated. The in vitro aging model was constructed using bleomycin (BLM) in vascular smooth muscle cells (VSMCs). Cell senescence were assessed through Western blotting analysis of aging markers, flow cytometry, and the β-galactosidase (SA-β-Gal) kit. Mitophagy was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Furthermore, CsA significantly inhibited the expression of mitophagy markers (PINK1, parkin, and LC3) and aggravated the damage of renal function induced by IR, thereby suggesting the role of mitophagy in the recovery process. In addition, AS-IV was shown to play a protective role by promoting mitophagy, which reduced the accumulation of damaged mitochondria in a vascular senescence model ( 42 ). Our results confirmed that AS-IV administration reduced ROS production, enhanced mitophagy, and attenuated the renal functional deficits and histopathological changes induced by IR.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CsA significantly inhibited the expression of mitophagy markers (PINK1, parkin, and LC3) and aggravated the damage of renal function induced by IR, thereby suggesting the role of mitophagy in the recovery process. In addition, AS-IV was shown to play a protective role by promoting mitophagy, which reduced the accumulation of damaged mitochondria in a vascular senescence model ( 42 ). Our results confirmed that AS-IV administration reduced ROS production, enhanced mitophagy, and attenuated the renal functional deficits and histopathological changes induced by IR.…”
Section: Discussionmentioning
confidence: 99%
“…Senescent VSMCs are abundant in atherosclerosis plaques and the vascular wall of the artery disease model [ 42 , 61 ]. Defective mitophagy leads to the accumulation of impaired mitochondria, which is the primary source of mtROS and ultimately contributes to the senescence of VSMCs [ 62 ]. P53 can bind to PINK and prevent its transport to mitochondria, which leads to impaired mitophagy mediated by PINK/Parkin [ 63 ].…”
Section: Mitophagy Of Vsmc In Vascular Remodelingmentioning
confidence: 99%
“…P53 can bind to PINK and prevent its transport to mitochondria, which leads to impaired mitophagy mediated by PINK/Parkin [ 63 ]. It has been shown that activation of PINK/Parkin-mediated mitophagy can alleviate the senescence of VSMCs [ 62 ]. In addition to PINK, an AMPK/SIRT1 signal protects mitophagy by improving bioenergy efficiency [ 63 ].…”
Section: Mitophagy Of Vsmc In Vascular Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018) found that a 30‐day or lifetime dietary intervention with ursolic acid improved the lifespan and climbing ability of Drosophila , the effect that required the stl gene ( Drosophila homolog of PGC‐1α). Astragaloside IV, present in Astragalus membranaceus , reduced inflammatory cell infiltration and β ‐galactosidase levels in the vascular smooth muscle of d ‐galactose‐induced aged mice when intervened at doses of 20/40/80 mg/kg/d (Li et al., 2022). Further, mechanistic investigation through cellular models revealed that the antiaging effect of astragaloside IV on vascular smooth muscle was dependent on Parkin‐mediated mitophagy activation.…”
Section: Antimuscle Aging Effects Of Natural Dietary Products Targeti...mentioning
confidence: 99%